Unemployment Flows, Participation and the Natural Rate for Turkey - Gonul Sengul; Murat Tasci (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
This paper measures flow rates into and out of unemployment for Turkey and uses these rates to estimate the unemployment rate trend, that is the level of the unemployment rate the economy converges to in the long-run. In doing so, the paper explores the role of the labor force participation in determining the trend unemployment. We find an inverse V-shaped pattern for the unemployment rate trend over time in Turkey, currently standing between 8.5 and 9 percent, with an increasing labor market turnover. We also find that allowing for an explicit role for participation changes the results substantially, reducing the "natural" rate at first, but then getting closer to the baseline over time. Finally, we show that this parsimonious model can be used for forecasting unemployment in Turkey with relative ease and accuracy.
Keywords: C3; G2; 330; Risk measurement; systemic risk; connectedness; systemically important financial institutions; vector autoregression; variance decomposition